2015
DOI: 10.1097/crd.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Review of the Treatment of Cardiovascular Disease in People With Hemophilia A and B

Abstract: With advances in care, increasing numbers of people with hemophilia (PWH) achieve near-normal life expectancies and present with typical age-related cardiovascular conditions. Evidence-based guidelines for medical or surgical management of cardiovascular conditions in individuals with hemophilia are limited. Published recommendations exist for the management of some common cardiovascular conditions (eg, ischemic heart disease, atrial fibrillation), but identifying optimal strategies for anticoagulant or antith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(116 citation statements)
references
References 127 publications
(224 reference statements)
2
110
0
4
Order By: Relevance
“…Because dual antiplatelet therapy has a bleeding risk comparable to warfarin, 40 we do not typically use dual antiplatelet therapy without prophylactic factor replacement, especially in patients with more-severe variants of VWD. Although published approaches have recommended maintenance of a trough factor level at .30% in hemophilia (Table 1), 1,34,[41][42][43] we have found that patients tolerate dual antiplatelet therapy with somewhat lower troughs, and by doing so, we avoid the frequent higher peak levels of FVIII that are necessary to achieve troughs of this magnitude, thereby improving patient compliance and reducing the thrombotic risk. Further, data from The Netherlands have shown that spontaneous (although not traumatic or anticoagulant-induced) bleeding is eradicated in mild to moderate hemophilia when the factor level is .15%…”
Section: Af In Bleeding Disordersmentioning
confidence: 99%
“…Because dual antiplatelet therapy has a bleeding risk comparable to warfarin, 40 we do not typically use dual antiplatelet therapy without prophylactic factor replacement, especially in patients with more-severe variants of VWD. Although published approaches have recommended maintenance of a trough factor level at .30% in hemophilia (Table 1), 1,34,[41][42][43] we have found that patients tolerate dual antiplatelet therapy with somewhat lower troughs, and by doing so, we avoid the frequent higher peak levels of FVIII that are necessary to achieve troughs of this magnitude, thereby improving patient compliance and reducing the thrombotic risk. Further, data from The Netherlands have shown that spontaneous (although not traumatic or anticoagulant-induced) bleeding is eradicated in mild to moderate hemophilia when the factor level is .15%…”
Section: Af In Bleeding Disordersmentioning
confidence: 99%
“…8 Coagulation factor levels must be monitored closely after the procedure and with appropriate factor replacement, maintain the levels of 80%-100% while on therapeutic doses of anticoagulation and trough levels of at least ≥30% when patients are on DAPT (aspirin + P2Y 12 inhibitors) and ≥5%-10% when on aspirin alone. 8 Coagulation factor levels must be monitored closely after the procedure and with appropriate factor replacement, maintain the levels of 80%-100% while on therapeutic doses of anticoagulation and trough levels of at least ≥30% when patients are on DAPT (aspirin + P2Y 12 inhibitors) and ≥5%-10% when on aspirin alone.…”
Section: Dear Editormentioning
confidence: 99%
“…Hemophilia A and B affect about 1 in 5,000 to 10,000 and 1 in 40,000 males at birth. Disease severity depends on the plasma concentrations of FVIII or FIX, where severe, moderate, and mild disease are characterized by plasma concentrations <1% activity of normal (<0.01 U/l; usually associated with spontaneous unprovoked bleeding episodes), 1–5% activity of normal (0.01–0.05 U/l), and 5–40% of normal (0.05–0.3 U/l) respectively . Patients with moderate or mild disease typically present with bleeding after trauma or surgery.…”
Section: Introductionmentioning
confidence: 99%